The dentist of Auschwitz : a memoir - Jacobs, Benjamin, 1919-2004 (University Press of Kentucky, 1995)
"In 1941 Berek Jakubowicz (now Benjamin Jacobs) was deported from his Polish village and remained a prisoner of the Reich until the final days of the war. His possession of a few dental tools and rudimentary skills saved his life. Jacobs helped assemble V1 and V2 rockets in Buchenwald and Dora-Mittelbau; spent a year and a half in Auschwitz, where he was forced to remove gold teeth from corpses; and survived the RAF attack on three ocean liners turned prison camps in the Bay of Lubeck. This is his story